A memória nos contos Quem manda aqui? e Maundlane, o Criador de Paulina Chiziane - Costa, Márcia Neide dos Santos (2018)
As andorinhas (2013) is a book of short stories written by a Mozambican author named Pauline Chiziane, which has broad issues to be discussed, for instance: decolonization, nationalism, the crisis of the contemporary subject, identity development, gender etc. As andorinhas is a work in which it is possible to explore the author's narrative, as much as her metaphors, amongst other aspects. Because of the abundance of historical and cultural aspects present in the book, we chose to work with the aspect of memory as a main subject. Therefore, the objective of this work is to analyze the presence of this aspect in the following short stories: Quem manda aqui?andMaundlane, o Criador, which compose the corpus of this study. Using the mechanism of the memory, we reflect on the manner in which Paulina Chiziane questions and problematizes the model of the colonizer and the History of the Mozambican nation. This manner can be noticed, through irony, where resides what is and what is not said, which is presented as an aesthetic, political and discursive tool. To substantiate the discussions we used the ideas of: Nádia Battella (1985), Le Goff (1996), Ecléia Bosi (2012), Michael Pollak (1992), Pires Laranjeira (1995), Thomas Bonnici (2005), Inocência da Mata (2014), Linda Hutcheon (2000), Lélia Duarte (1994) and authors who criticize the work of Chiziane such as: Laura Padilha (2013), Maria Geralda de Miranda (2013), Carmem Lúcia Secco (2013), Cândido Rafael (2013), amongst others.